Should Antithrombotic Treatment Strategies in East Asians Differ from Caucasians? - Bae, Jae S.; Ahn, Jong-Hwa; Tantry, Udaya S.; Gurbel, Paul A.; Jeong, Young-Hoon (Current Vascular Pharmacology, 2018)
With over 1.5 billion people, East Asians are the most populous race in the world. Health status in this population is an important global issue. In the contemporary trials of antithrombotic treatment, East Asian patients have a lower risk for atherothrombotic diseases (especially, Coronary Artery Disease [CAD]) and a higher risk for bleeding (especially, gastrointestinal bleeding and hemorrhagic stroke). Despite these observations, antithrombotic treatment strategies in East Asian patients are mainly based on the American or European guidelines that are derived from randomized, controlled trials including mostly Caucasians. Despite a low response to clopidogrel, East Asian patients with CAD show a similar or even a lower rate of ischemic event occurrence and higher bleeding risk compared with Caucasian patients. The latter is referred to as the “East Asian Paradox”, suggesting a dissimilar therapeutic window for antiplatelet therapy than Caucasians. In addition, different net clinical benefits have been observed between the races with potent P2Y12 inhibitors that may be related to racial differences in pharmacokinetic and pharmacodynamic profiles. Furthermore, there is emerging concern regarding differences between East Asian vs. Western patients in pharmacodynamic and clinical efficacies of anticoagulant agents. We now summarize experimental and clinical evidence of the efficacy and safety of antithrombotic agents in the East Asian population. We suggest the concept of “race-tailored antithrombotic treatment” in CAD patients and/or in patients undergoing percutaneous coronary intervention.
Keywords: coronary artery disease